2008
DOI: 10.1186/1472-6963-8-128
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of a visiting service for older widowed individuals: Randomised trial

Abstract: Background: Despite a growing understanding of the effectiveness of bereavement interventions and the groups that benefit most from them, we know little about the cost-effectiveness of bereavement interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Net significant QALY gains of 0.011 in the intervention group ( p < 0.05)Health-care payer perspectiveIncremental cost per QALY gained of €17 174C: No invitation to participate24 monthsCUAThe incremental annual cost of the programme was €253 700 per 10 000 participants2004. Euros, €s(Onrust et al , 2008), NetherlandsI: Visiting service for older widow/ers bereaved for 6–9 months consisting of 10–12 home visits by a trained volunteer. Based on the Widow to Widow Programme138 widows/78 widowers; 110 in the intervention group; 106 in the control group; Mean age of participants 68.8 (range 50–92)RCTAnnual costs of intervention €553 per participant.Quality of life measured using EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
“…Net significant QALY gains of 0.011 in the intervention group ( p < 0.05)Health-care payer perspectiveIncremental cost per QALY gained of €17 174C: No invitation to participate24 monthsCUAThe incremental annual cost of the programme was €253 700 per 10 000 participants2004. Euros, €s(Onrust et al , 2008), NetherlandsI: Visiting service for older widow/ers bereaved for 6–9 months consisting of 10–12 home visits by a trained volunteer. Based on the Widow to Widow Programme138 widows/78 widowers; 110 in the intervention group; 106 in the control group; Mean age of participants 68.8 (range 50–92)RCTAnnual costs of intervention €553 per participant.Quality of life measured using EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
“…() identified a small short‐term effect on depression symptoms, which is also consistent with the finding of this study. However, previous studies with carers and those recently bereaved did not find befriending or social support reduced anxiety symptoms as this study found (Charlesworth et al ., ; Onrust, Smit, Willemse, van den Bout, & Cuijpers, ). It may be that for those with COPD, social support works differently than in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…7 In another trial based on peer support among widows, the experimental group slightly improved against slightly higher costs. 15 Therefore, the service would be acceptable depending on the willingness to pay per QALY gained. Further research should help to distinguish which specific subgroups could benefit the most considering the diversity of interventions and contexts.…”
Section: Costsmentioning
confidence: 99%